Управління у сфері поводження з відходами в умовах переходу до економіки замкненого циклу в Україні - Zamlynskyi, Victor A. (Dr. Viktor Koval, 2020)
Monograph Review “MANAGEMENT IN THE FIELD OF WASTE MANAGEMENT IN THE CONDITIONS OF TRANSITION TO THE CIRCULAR ECONOMY IN UKRAINE” by Authors Viktor Koval, Inessa Mikhno and Mariana Petrova